The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2514/1.26402
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Ignition of Thermally Cracked Kerosene in Supersonic Model Combustors

Abstract: A series of experiments were conducted to characterize the self-ignition and combustion of thermally cracked kerosene in both a Mach 2.5 model combustor with a combustor entrance height of 51 mm and a Mach 3.0 model combustor with an entrance height of 70 mm. A unique kerosene heating and delivery system was developed, which can prepare heated kerosene up to 950 K at a pressure of 5.5 MPa with negligible fuel coking. The extent of China no. 3 kerosene conversion under supercritical conditions was measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…The working pressure of the aviation kerosene generally exceeds its critical pressure, above which no phase transition will occur. The state of an aviation kerosene changes from liquid state to supercritical state at the supercritical pressure with the increase of temperature, and then steps into thermal cracking state with further increase of temperature [3]. The specific heat capacity of supercritical fluid has a peak value when it varies with temperature at a supercritical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The working pressure of the aviation kerosene generally exceeds its critical pressure, above which no phase transition will occur. The state of an aviation kerosene changes from liquid state to supercritical state at the supercritical pressure with the increase of temperature, and then steps into thermal cracking state with further increase of temperature [3]. The specific heat capacity of supercritical fluid has a peak value when it varies with temperature at a supercritical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Regenerative fuel cooling has been considered one of the most effective and practical methods for hydrocarbonfueled scramjets [1][2][3]. In a regenerative cooling system, before injection into combustor, the fuel flows through the cooling channels along the combustor wall, carrying away heat from the wall via heat convection and endothermic chemical reactions (thermal cracking) [4,5]. A challenge for regenerative cooling systems is that the amount of the fuel used as coolant must match that used for the combustion.…”
Section: Introductionmentioning
confidence: 99%
“…When the fuel temperature is sufficiently high, the fuel pyrolysis occurs as well [7]. Experimental results [6,8] demonstrated that the overall burning intensity as well as the combustion efficiency improved with supercritical/cracked kerosene injection. However, further enhancement in combustion efficiency was limited by the shorter penetration depth of supercritical/cracked kerosene due to the lower density.…”
mentioning
confidence: 92%